2023
DOI: 10.2147/idr.s390996
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Perception and Acceptance Among Female Medical and Nursing Students at Al-Azhar University, Egypt

Abstract: Background There are still many concerns related to various types of COVID-19 vaccines, which may result in individuals’ hesitancy presenting a problem for public health authorities to achieve coverage for population immunity. As trustworthy health-care workers, medical and nursing students’ perception towards COVID-19 vaccines may greatly influence the future population’s uptake of vaccines; however, studies related to the vaccine acceptance rates among them are limited. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These findings are coherent with previous studies. 32 , 33 , 34 One explanation for this might be the nature of their background, where a more clinical approach is required. Therefore, medical students would have the opportunity to acquire greater insight, and have a greater sense of responsibility for themselves and for others.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are coherent with previous studies. 32 , 33 , 34 One explanation for this might be the nature of their background, where a more clinical approach is required. Therefore, medical students would have the opportunity to acquire greater insight, and have a greater sense of responsibility for themselves and for others.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is because of the many types of Covid-19 vaccines circulating from several companies, giving rise to doubts about the effectiveness of each of these vaccines. 3 In addition, trust in vaccines is also very dependent on feelings of trust in governments, health professionals, scientific authorities, and strong scientific data. 2 …”
Section: Dear Editormentioning
confidence: 99%
“…Another reason is because of the many types of Covid-19 vaccines circulating from several companies, giving rise to doubts about the effectiveness of each of these vaccines. 3 In addition, trust in vaccines is also very dependent on feelings of trust in governments, health professionals, scientific authorities, and strong scientific data. 2 The study conducted by Shane Khan et al was a cross-sectional study in which participants had to complete an adapted WHO questionnaire on reasons for hesitancy of the COVID-19 vaccine.…”
mentioning
confidence: 99%
“…Highly reliable clinical evidence derived from randomized clinical trials confirmed that Sinopharm vaccine reduced the incidence of symptomatic COVID-19 [ 10 ]. Regrettably, the acceptance and immunization rates for COVID-19 vaccines in Egypt are reportedly low [ [11] , [12] , [13] ]. The present study aimed to compare the rate of reinfection after two and three doses of Sinopharm COVID-19 vaccine in HD patients.…”
Section: Introductionmentioning
confidence: 99%